Assessing the levels of certain elements (Na, K, Ca, Mg, Fe, and Zn) in a variety of baby formula brands available in Libya - Badria. A. Salem; Rowaida M. Younes (Libyan Journal of Medical and Applied Sciences, 2025)
According to the World Health Organization, breastfeeding is the healthiest and safest option for newborns. Infant formulas continue to be a great substitute for breast milk and serve a crucial function in the baby’s nutrition. Purified bovine milk, protein, lactose, vegetable oils, and vitamin/mineral premixes are the main components of baby formulae. Due to the possibility that adding extraneous ingredients or serving sizes may have an impact on a baby’s physiological and metabolic processes. In ten samples of powdered infant milk formulas (0–6 months) available on the Libyan market, the concentration of many elements, including sodium, potassium, calcium, iron, and magnesium, was measured using a flame photometer. The results were compared to the label values. The results of this investigation, which took place in 2024, showed that while the contents of zinc, iron, and magnesium were lower than those stated on the label in all formulas and below Codex alimentarius requirements, the contents of sodium, calcium, and potassium were more than those declared on the label in all formulas and met Codex alimentarius requirements.